ENHANCING THE SCIENTIFIC LEVEL OF ENGINEERING TRAINING OF RAILWAY TRANSPORT PROFESSIONALS - Kalivoda, J.; Neduzha, L. O. (Science and Transport Progress, 2017)
Purpose. Publication of the results of international scientific and technical cooperation of the Dnipropetrovsk National University of Railway Transport named after Academician V. Lazaryan (DNURT, Ukraine) and the Czech Technical University (CTU) in the field of engineering training of students on the basis of modern methods of development of scientific and creative abilities of students. Methodology. The development of scientific thought and the improvement of the professional level of students of engineering specialties of railway technical institutes may be carried out by different methods both during training and during extracurricular time. One of the methods for improving the scientific level of future engineers is the public lectures of renowned scholars and researchers from leading European higher education institutions, enabling students to have access to world-class advanced scientific idea. Findings. The authors have analyzed the activity of DNURT and CTU on scientific and educational preparation of students. It is emphasized that cooperation promotes strengthening of contacts between universities, improves the quality of students’ training, is one of the factors of the professional development of future specialists, raising the scientific level of engineering training of railway transport professionals. It is proved that DNURT and CTU duly fulfill the higher education tasks of training of professional personnel who are able to work effectively in the global market, aimed at improving the quality and efficiency of education. Originality. This paper presents the analysis of results concerning the efficiency of application of modern methods for engineering training of students of technical higher educational institutions. It gives extended view of the main directions of international education activities. Practical value. It is confirmed that popularization of modern methods of propagation of engineering thought among student youth has acquired a new meaning and contributes to enhancing the scientific level of engineering training of railway transport professionals.